The Impact of Industrialization on Secondary Schooling during the Industrial Revolution: Evidence from 19th Century France - Raphaël Franck (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study explores the impact of industrialization on secondary schooling in 19th century France. As a source of exogenous variation in industrialization across the French territory, it takes advantage of the openings and closures of mines which were supervised by the Ministry of Public Works, independently from the Ministry of Education. The results suggest that industrialization had a negative but mostly insignificant effect on high-school enrollment. However, industrialization increased the share of high-school pupils in applied sections and the wages of mathematics teachers.
Keywords: I25; N33; O14; 330; horse power; industrial revolution; secondary schooling